Breast Cancer among Pakistani Women in Referral Hospitals: An Overview of Risk Factors (Ibrahim Medical College Journal, 2010)
The aim of this study was to determine the significance of various reproductive risk factors amongstPakistani women suffering from breast carcinoma. This observational study was carried out fromMarch 2007 to February 2009 at three hospitals. The women who presented with breast swellingwith or without discharge from nipple were included in the study. The diagnosis of breast cancer wasconfirmed by histopathological examination. A questionnaire included history and various reproductiverisk factors. The study patients were divided into two groups by their menopausal history – premenopausaland post-menopausal as ‘group A’ and ‘group B’, respectively. A total of 70 patients hadthe diagnosis of breast cancer. Of them, 32 were in group A and 38 in group B. Regarding agedistribution, 49% were found in ≥51 years of age and 29% in the age group 30 – 40 years. The meanage at menarche was 13.3 years in group A and 12.4 years in group B. Nulliparity was seen in12.5% cases in group A and 5.26% in group B. History of first full term pregnancy (FFTP) belowthe age of 20 was present in majority of cases in both groups though higher in group B. Breast cancerin post-menopausal women was exclusively found among those who had early menarche (